2008
DOI: 10.1152/ajpheart.00082.2008
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase control mechanisms in the cutaneous vasculature of humans in vivo

Abstract: Nitric oxide (NO) participates in locally mediated vasodilation induced by increased local skin temperature (T(loc)) and in sympathetically mediated vasodilation during whole body heat stress. We hypothesized that endothelial NOS (eNOS) participates in the former, but not the latter, response. We tested this hypothesis by examining the effects of the eNOS antagonist N(G)-amino-l-arginine (l-NAA) on skin blood flow (SkBF) responses to increased T(loc) and whole body heat stress. Microdialysis probes were insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
110
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 47 publications
12
110
0
1
Order By: Relevance
“…15,16 The results of the present study examining dorsal foot skin perfusion concur with these observations related to the effects of localized heating on forearm skin responses. With regard to the interactions of NO and PG on skin vasodilation, in healthy humans, chronic low-dose aspirin therapy attenuates the reflex cutaneous vasodilation during whole-body heating that is mediated through both the cyclooxygenase-dependent pathway of PG formation and NO synthase-dependent mechanisms.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…15,16 The results of the present study examining dorsal foot skin perfusion concur with these observations related to the effects of localized heating on forearm skin responses. With regard to the interactions of NO and PG on skin vasodilation, in healthy humans, chronic low-dose aspirin therapy attenuates the reflex cutaneous vasodilation during whole-body heating that is mediated through both the cyclooxygenase-dependent pathway of PG formation and NO synthase-dependent mechanisms.…”
supporting
confidence: 90%
“…17 While vasodilation of skin in response to local heating is highly NO-dependent, it may also reflect the i nteraction of NO and PG. 15,18 Cutaneous acetylcholine-mediated endothelium-dependent vasodilation has been reported to be highly NO-dependent and also strongly related to the interactions of NO with prostaglandins. 18 Thus, an interaction between these two vasodilatory compounds during localized heating of dorsal foot skin to 44°C is also a possibility, albeit an untested one, in this study.…”
mentioning
confidence: 99%
“…Figure 1 shows a representative trace of SkBF changes throughout the experiment in part 1. After dosing at the final concentration, SNP (Sigma) dissolved in sterile saline at a concentration of 56 mM was administered for 30 -40 min via microdialysis at a rate of 4 l/min, which has previously been shown to elicit maximal SkBF (20,21). As an additional study in part 1, to confirm whether the SNP dose following the administration of NE at a higher concentration can elicit maximal vasodilation, the SNP dose was performed without pretreatment of NE in six subjects.…”
Section: Subjectsmentioning
confidence: 99%
“…Additionally, the initial peak has been shown to have nitric oxide and noradrenergic sympathetic nerve components (Minson et al 2001;Houghton et al 2006;Hodges et al 2008Hodges et al , 2009bTew et al 2011b). Kellogg et al (1999) determined that the plateau phase of the cutaneous vasodilator response is ∼70% dependent on NO and have recently shown that the vasodilatation in response to local skin heating is produced by endothelial NO synthase (eNOS; Kellogg et al 2008Kellogg et al , 2009.…”
mentioning
confidence: 99%